Digital Health Solutions: An Important Tool in Patient Engagement. Issue 6 (June 2016) - Fox, Brent I.; Pinto, Brian
Hospitals and health systems are facing increased pressure to improve quality and outcomes while reducing expense. Quality-based reimbursement models are providing the necessary incentives for health care institutions to focus on issues such as avoidable hospital-acquired conditions and 30-day readmission rates. While our health care facilities certainly play a vital role in achieving optimal outcomes, patient engagement remains at the center of these efforts.